Frontier Discoveries and Innovations in Interdisciplinary Microbiology - Shukla, Pratyoosh (Springer India : Imprint: Springer, 2016)
This excellent book covers wide-ranging topics in interdisciplinary microbiology, addressing various research aspects and highlighting advanced discoveries and innovations. It presents the fascinating topic of modern biotechnology, including agricultural microbiology, microalgae biotechnology, bio-energy, bioinformatics and metagenomics, environmental microbiology, enzyme technology and marine biology. It presents the most up-to-date areas of microbiology with an emphasis on shedding light on biotechnological advancements and integrating these interdisciplinary microbiology research topics into other biotechnology sub-disciplines. The book raises awareness of the industrial relevance of microbiology, which is key component of this unique collection. The topics include production of antioxidant-glutathione, enzyme-engineering methods, probiotic microbiology and features of microbial xylanases. It also covers some other remarkable aspects of microbiology, like potential health hazards in recreational water and fullerene nanocomposites, which are vital for biotechnological interventions. This book will be valuable resource for senior undergraduate and graduate students, researchers and other interested professionals or groups working in the interdisciplinary areas of microbiology and biotechnology.